Forest Degradation Under Global Change - Samec, Pavel (Sustainable Development, 2023)
Human activities cause the degradation of innumerable ecosystems, including forests. The degradation of forests leads to far-reaching nutrient cycle changes throughout all environments. Reversible or irreversible degradation processes cause declines in an ecosystem's ability to self-regulate. Reversible processes decrease native forest biodiversity while preserving the ecosystem's abiotic components, whereas irreversible processes alter the character of the potential natural vegetation. This book discusses forest degradation in three sections on general, climatic, and land-use degradative effects.